Mapping Corporate Governance in Indonesia: A Guide for Future Research - Moh. Halim; Rendy Mirwan Aspirandi; Riyanto Setiawan Suharsono (JKEN: Jurnal Kajian Ekonomi Nasional, 2025)
The implementation of Good Corporate Governance (GCG) in Indonesia faces various challenges despite the existing regulations. Key issues include transparency, accountability, and the strong political influence in corporate decision-making. This study aims to analyze the application of GCG principles in Indonesia, identify the barriers, and provide recommendations for strengthening the effective implementation of governance. Using a narrative review approach, this research examines various previous studies related to corporate governance in Indonesia. The findings show that, although GCG regulations in Indonesia have evolved, their implementation is often hindered by weak oversight, political influence, and discrepancies between theory and practice. Additionally, the findings underscore the importance of the roles of the board of commissioners, audit committees, and external oversight in improving GCG implementation in Indonesia. This study contributes by enhancing the understanding of the gap between corporate governance theory and practice in Indonesia and offers more practical recommendations for policymakers and practitioners to improve corporate transparency and accountability. The research also provides new insights into the development of governance theories more relevant to Indonesia's context. Keywords: Good Corporate Governance, Transparency, Accountability, Political Influence, Indonesia, Narrative Review